Mechanisms and prospects of circular RNAs and their interacting signaling pathways in colorectal cancer - Wang, Shuwei; Cheng, Liang; Wu, Haotian; Li, Gan (Frontiers in Oncology, 2022)
Colorectal cancer (CRC) is the leading malignant tumor in terms of morbidity and mortality worldwide, and its pathogenesis involves multiple factors, including environment, lifestyle, and genetics. Continuing evidence suggests that circular RNAs (circRNAs), as a novel non-coding RNA, constitute an important genetic variable in the pathogenesis of CRC. These circRNAs with covalently closed-loop structures exist objectively in organisms. They not only have the biological functions of regulating the expression of target genes, changing the activity of proteins, and translating proteins, but also play a key role in the proliferation, invasion, migration, and apoptosis of tumor cells. CRC is one of the most common cancers in which circRNAs are involved in tumorigenesis, metastasis, and drug resistance, and circRNAs have been demonstrated to function through crosstalk with multiple signaling pathways. Therefore, this review summarizes the biological and carcinogenic functions of circRNAs and their related PI3K/AKT, MAPK, Notch, JAK/STAT, Hippo/YAP, WNT/β-catenin, and VEGF signaling pathways in CRC. We further explore the clinical value of circRNAs and important signaling proteins in the diagnosis, prognosis, and treatment of CRC.